Optimal Transmission Regulation in an Integrated Energy Market - Thomas P. Tangerås (Research Institute of Industrial Economics (IFN), 2010)
The capacity of the transmission network determines the extent of integration of a multinational energy market. Cross-border externalities render coordination of network maintenance and investments across countries valuable. Is it then optimal to collect powers in the hands of a single regulator? Should a common system operator manage the entire network? I show that optimal network structure depends on (i ) how the common regulator would balance the interests of the different member states; (ii ) how the gains from market integration vary across countries; (iii ) network characteristics (substitutability versus complementarity); and (iv ) the social cost of operator rent.
Keywords: D62; D82; L51; L94; 330; Multi-national Energy Market; Transmission; Supranational Regulation; System Operation; Multi-contracting; Energiemarkt; Regulierung; International; Externer Effekt; Asymmetrische Information; Regulierungstheorie